The Study of Realationship between Scientific Research and the Needs of Iranian Rural Communities with an Emphasize on Geography and Rural Planning Dissertations - Masood Niksirat; Seayed Ali Badri (نشریه جغرافیا و برنامه‌ریزی, 2015)
The first prerequisite for the success of the rural researches is correct understanding and suitable perception of the needs of local communities. The part of the country's rural researches includes thesis and dissertation of students in geography and rural planning. In this article, we examine the relationship between the thesis and dissertation with the needs of rural communities and try to provide a model for rural researches in Iran. The methodology is descriptive-analytical which was conducted to combine two documentary and survey methods. The statistical population includes student population (N=161) and faculty stafs (N=20) in the field of rural geography and planning at three universities (University of Tehran, Shahid Beheshti University and Tarbiat Modarres University). Research results show that the majority of academic advisors in theses/dissertations believed that there was a relationship between the subjects selected for the research and the needs of rural communities but the results of the most important factor in selecting theses/dissertations’s subject showed that students have less attention to the needs of rural communities. Financial constraints (financial problems of students), weighing 0.249 was the most important limitation of the students to choose issues on rural communities’ needs. Accordingly, the proposed model for carrying out rural research in Iran was presented.